O feminismo e o feminino em Um útero é do tamanho de um punho, de Angélica Freitas - Barbosa, Elionete Rodrigues (2021)
This study intends to analyze the representations of the feminine in the work Um útero é do tamanho de um punho (2012), written by Angélica Freitas, through an analytical-descriptive research that has among its objectives to identify, in terms of content and form, the permanencies and ruptures of the feminine and the problematization of the patriarchal culture in the referred book. Given the above, in the search for the right to equality between genders and their identities, it is worth highlighting movements and languages that struggle in their different forms, including literature. For that, as a theoretical apparatus that supports the analyzes presented here, on the themes of the feminine and feminism, we counted on the contributions of Simone de Beauvoir (2016); Betty Friedan (1979); Judith Butler (2006) and Naomi Wolf (2019), among others. The studies carried out by the aforementioned authors guided the understanding of the representations of feminist thought and its trajectory in literature, which gave shape to the feminine contained in the poems chosen for this study. Thus, it was possible to identify how much the myths surrounding this representation are present and quite coherent with the theoretical discussions presented by the referred theorists. Angelica, in a unique way, describes in her verses this feminine universe, with emphasis on the woman's body and all the problems arising from it. Through the representation of the body (uterus), the poet develops in her poems the theme of identities using resources such as irony, humor and the obscene. Through everyday elements and clichés, it seeks to provoke in the reader reflections on paradigms imposed on the female universe even in the contemporary world, showing how the vision of women retains traces of a heritage of tradition that continues to reinforce her inferior place in society.